Parents' Views to Strengthen Partnerships in Newborn Intensive Care - Ferreira, Alexie; Ferretti, Emanuela; Curtis, Krista; Joly, Cynthia; Sivanthan, Myuri; Major, Nathalie; Daboval, Thierry (Frontiers in Pediatrics, 2021)
Background: Parental involvement in their newborn’s neonatal intensive care reduces stress and helps with the parent-child attachment, transition to home, and future development. However, parents’ perspectives are not often sought or considered when adapting family-centered care in neonatal intensive care units (NICUs). Aim: To identify what parents believe helps or hinders their involvement in their newborn’s care when admitted to our Level 3B NICU. Methods: Between August and October 2018, nine mothers and one father were interviewed during three 60- to 90-minute audiotaped focus groups using a semi-structured interview tool. From the content analysis of the verbatims, three reviewers identified key themes that affected how involved parents could be in their newborn’s care. Results: Parents provided examples of factors that facilitated or restricted their involvement. The analysis identified themes: 1) parent-staff interactions, 2) supportive/trustworthy healthcare professionals, 3) consistency in care and caring staff, 4) family, couple, and peer support, 5) newborn status, 6) resources and education for parents, 7) the NICU environment, and 8) academic and research participation. Conclusion: We identified a conceptual framework to allow our NICU team to prioritize working strategies to strengthen parental involvement in newborn care. In addition to implementing ways to involve parents, we need to address parents’ satisfaction with their participation. These findings may help other investigators explore parents’ expectations toward their NICU experience.